Analisis Perkembangan Fisik Terhadap Keaktifan Siswa Kelas V di SDN 1 Karangmangu Susukan Lebak Cirebon - Syahfa Azahra; Syifa Ummuhani; Nurkholis (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to examine the physical development conditions of elementary school-aged students at SDN 1 Karangmangu, in order to support the creation of an optimal learning process through the strengthening of children's physical aspects. Physical development is understood as a biological change that includes the growth of muscles, the brain, and bones. The role of teachers and parents is crucial in stimulating and monitoring this development, so that children can grow into independent individuals in adulthood. The method used in this research is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The research location is SDN 1 Karangmangu, with participants being the students of the school, and analysis is conducted based on child physical development theory. The results of the study show that, in general, the physical development of students is progressing well, although some children experience growth that is not in accordance with their age. These differences are suspected to be influenced by genetic and environmental factors. Therefore, parental involvement is essential in guiding children's physical development towards a more optimal direction.